Strategies to control the high temperature shrinkage of fly ash based geopolymers - Vickers, Les; Rickard, William D.A.; van Riessen, Arie (Elsevier Science, 2014)
Strategies to control thermally induced shrinkage in fly ash based geopolymers are investigated. The useof low (<2) Si:Al ratios in the geopolymer provides superior thermal properties and the addition of fillers delivered additional improvements resulting in impressive thermal resistance. Two thermally stable inorganic fillers, α-alumina and wollastonite, were used because of their high melting points and relatively low thermal expansion. Shrinkage events at elevated temperatures revealed that samples containing filler exhibited 30–35% less volume shrinkage than the control at 1000 °C. Initial compressive strength was moderate (~30 MPa), but increased markedly when samples were fired in excess of 600 °C >100 MPa). Wollastonite addition also improved the flexural strength of the samples which was attributed to its acicular shape imparting fibre-like qualities. Microstructural investigations showed that unfired samples predominantly consisted of spherical particles coated with reaction product. Firing to 1000 °C converted the morphology to a more compact phase with increased pore size.